(untitled) (Research, Society and Development, 2021)
This paper aims to discuss the perspectives of the Mathematics undergraduates in constitution of teaching, against the low social prestige, professional precariousness and recent changes in educational policy for teacher training, proposed by the BNCC. The reviews that will be presented result from a qualitative approach research, carried out in a federal public institution of higher education, located in the metropolitan region of a state in the country’s northeast . For data production, we chose focus groups, questionnaires and the content analysis technique. The results found point the need to prevent the ongoing process of teaching peripheralization and the urgent need to build a proposal for initial teacher education focused on the reality of young working students.